4t+6=5t+1

Simple and best practice solution for 4t+6=5t+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4t+6=5t+1 equation:


Simplifying
4t + 6 = 5t + 1

Reorder the terms:
6 + 4t = 5t + 1

Reorder the terms:
6 + 4t = 1 + 5t

Solving
6 + 4t = 1 + 5t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-5t' to each side of the equation.
6 + 4t + -5t = 1 + 5t + -5t

Combine like terms: 4t + -5t = -1t
6 + -1t = 1 + 5t + -5t

Combine like terms: 5t + -5t = 0
6 + -1t = 1 + 0
6 + -1t = 1

Add '-6' to each side of the equation.
6 + -6 + -1t = 1 + -6

Combine like terms: 6 + -6 = 0
0 + -1t = 1 + -6
-1t = 1 + -6

Combine like terms: 1 + -6 = -5
-1t = -5

Divide each side by '-1'.
t = 5

Simplifying
t = 5

See similar equations:

| .3074= | | 74-6-t=25 | | .1523= | | .0789= | | 2-5/(3x-7)=2 | | t-8-4=31 | | 1.571428n=44 | | X=-16x^2+80x+0 | | 5y-19=2y+8 | | log(5x)-38=-28 | | 4b-6=6b | | -8(x-5)+2=-7x+7 | | 9x=(27/9)*6 | | 7(x+5)=8x+6 | | (23-3y)/(y-6) | | 9y-2=38+y | | 13x-(3x+12)-12x=-5x+3 | | -2(-3-x)=7 | | 2/3=x/25-x | | 13=2w+3(w+6) | | 6x+4=-28-2x | | -7v+5(v-3)=-23 | | 3x+19=3x-103 | | 12-t+25=23 | | 4*9-5y=26 | | G-5.2=-18.73 | | 4x-5(2)=26 | | 9-17+4x-x=0 | | 3(4x-3)-4(3x+8)=7(x-6) | | 12-4=5x-25 | | 75=P+3.75P | | 9+6=54153 |

Equations solver categories